Mortality Determinants in Severe Traumatic Brain Injury with Pneumonia: A Retrospective Study - Apriawan, Tedy; Armando, Alivery Raihanada; Kamaruddin, Muhammad Fadhil (Faculty of Medicine-Universitas Airlangga, 2025)
Introduction: Traumatic brain injury (TBI) is defined as an acute brain injury caused by mechanical forces to the head, excluding those related to drugs, alcohol, medications, or other conditions, such as systemic injuries, psychological trauma, or coexisting medical issues. TBI is a global public health issue responsible for significant disability and mortality, with an estimated global incidence of 69 to over 100 million new cases annually. This burden may be higher due to underreporting, particularly in low- and middle-income countries (LMICs). Several methods have been established to classify TBI, one of them is based on its severity with the Glasgow Coma Score (GCS). Pneumonia is a frequent complication in traumatic brain injury (TBI) patients, especially those on prolonged mechanical ventilation. Pneumonia could be classified based on the source of infection into ventilator-associated pneumonia (VAP), hospital-associated pneumonia (HAP), and community-acquired pneumonia (CAP). Objective: To evaluate the mortality and risk factors of severe traumatic brain injury (sTBI) with pneumonia. Methods: This study is a cross-sectional study with observational analytical investigations. The sample of this study is sTBI patients who were treated in Dr. Soetomo General Academic Hospital in 2023. Descriptive statistics were used to summarize the patients' characteristics. Chi-square tests and logistic regression were used to find relationship between factors that increase the risk of death and the development of pneumonia. Results: In 2023, we documented 832 TBI cases, of these, 479 cases (57.6%) were mild TBI, 273 cases (32.8%) were moderate brain injuries, while severe brain injuries (sTBI) with 80 cases (9.6%). Our study shows that 50% of patients with sTBI have pneumonia, and VAP itself is one of the contributing factors to mortality in this population (p<0.001). Conclusion: Of all types of pneumonia in this study, there is a statistical correlation between mortality and VAP in sTBI patients.